RİVAYETİN METNE DÖNÜŞTÜRÜLMESİNDE RAVİ TASARRUFUNA SEYF B. ÖMER’DEN ÖRNEKLER - İsrafil Balcı (İslami İlimler Dergisi)
This article deals with some narration of Saif b. Omar that is one of important sources of Tabari. These narrations are compared with those narrations taken place in other sources and then they are examined in terms of whether they are exposed to any changes or not. The reason for being chosen from Saif, he narrated differently from previous sources in many points. Thus, giving some examples from his works, it tries to indicate that how much a narrator or writer intervenes with the narration or not.